Necessary and Sufficient Condition for Stability of Generalized Expectation Value - Aziz El Kaabouchi; Sumiyoshi Abe (Journal of Applied Mathematics)
A class of generalized definitions of expectation value is often employed in nonequilibrium statistical mechanics for complex systems. Here, the necessary and sufficient condition is presented for such a class to be stable under small deformations of a given arbitrary probability distribution.